One Size Does Not Fit All: Lessons from a Case Study during COVID-19 - Park, Junpyo (Tauladan Fathimah Azzahra, 2024)
This research illustrates effective teaching approaches and modalities in higher education that were developed during the COVID-19 pandemic. Anonymous survey questionnaires, collected from 9 sections of college economics courses, reveal how students perceive their learning experiences. Survey responses from the students show that they enjoy different types of instructional strategies as well as the use of educational software like Flipped Classroom and HyFlex. Students also greatly appreciate a flexible and safe learning environment with clear organization, open communication, easy accessibility, and learning support. Finally, this paper discusses the students’ own opinions on future improvements for higher education as well as suggestions on education policy.